Emotional intelligence and anxiety, stress, and depression in first phase medical undergraduates - Kaushal Kumar Alam, (Asian Journal of Medical Sciences, 2023)
Background: Medical studies are one of the stressful course in India and worldwide. Emotional intelligence (EI) is a group of skills that can be learned to enhance coping skills and promote well-being. Aims and Objectives: The present study is aimed to analyze the relationship between EI and psychological distress such as depression, anxiety, and stress in 1st-year medical undergraduates. Materials and Methods: A self-reported questionnaire is used for assessing EI and psychological distress. A shorter version of the Trait EI questionnaire is used for assessing EI and the depression, anxiety, and stress subscale is used for assessing psychological distress. A total of 98 medical students participated in the study. Unpaired student’s t-test, ANOVA, and Pearson’s correlation coefficient analysis was performed. Results: The results showed a negative association between EI and depression, anxiety, and stress. Depression, anxiety, and stress were found in 35.7%, 50%, and 14.3% of 98 participants, respectively. EI was found to be significantly higher in men. Women were found to be more affected than men. Conclusion: High EI is associated with the lower psychological distress. This shows the need to assess and improve EI through practices that can improve their psychological health.